Audit services market: bibliometric analysis - Iryna; Gabriella Liudvykivna (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу, 2023)
Modern challenges in doing business and functioning of enterprises, implementation of sustainable development goals require adaptation of Ukrainian legislation to international, in particular European, standards, including the sphere of audit activities. An audit is a reliable way to confirm the reliability and confidence of information about the financial statements and financial condition of an enterprise. The article considers the regulatory framework for the concepts of «audit» and «audit activity». The market of audit services is studied and its components are identified: the provision of audit, non-audit and related services by audit entities. Along with this, the analysis of the audit services market and the problems of providing audit services and, directly, conducting an audit is carried out. In the course of the study, methods of visualization of the main areas of research of scientists, publication activity of authors based on data from the Scopus scientometric database using VOSviewer and Bibliometrix software were used. Bibliometric, structural, cluster, and graphical analyses were used. The applied research methods in the field of audit activity made it possible to identify the leading countries in terms of publication activity of the topic under study. The most cited articles are presented, which are aimed at determining the most relevant areas of research of scientists and further monitoring of problematic issues.